Persistent Hypotony Associated with Immunosuppressive Therapy in Glaucoma Drainage Implant Surgery - Susana Duch (Case Reports in Ophthalmology, 2016)
Purpose: To describe the histopathology of non-valved implant capsules in three cases of persistent postoperative hypotony after the restrictive tube ligature was released in patients receiving immunosuppressive therapy. Observations: The macroscopic appearance of the capsules 3 and 4 months postoperatively was immature and loose. Microscopic examination disclosed extremely irregular thin tissue, with thicknesses ranging from 0.02 to 0.6 mm, depending on the capsular location studied. Withdrawal of immunosuppressive therapy did not facilitate rebuilding of new capsules. Replacement with a valved implant device was necessary in two cases; the third case recovered with tapering of prednisone. Conclusions and Importance: The use of chronic systemic immunosuppressive therapy might interfere with capsular formation around the plates of drainage devices inducing persistent hypotony. In these cases, the use of valved implants might be safer.